Peningkatan Partisipasi Masyarakat dalam Program Pemenuhan Gizi Anak Berbasis Konsumsi Pangan sebagai Upaya Pencegahan Stunting - Dian Isti Angraini; Novita Carolia; Agustyas Tjiptaningrum; Intanri Kurniati (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this programme is to increase community participation in fulfilling balanced nutrition for children based on food consumption as an effort to prevent stunting. The method used is to increase the knowledge and educational skills of the community through interactive lectures and discussions, video screenings and educational games. This activity was carried out for 1 day and took place at the Nusantara Syariah Hotel, Bandar Lampung City. Participants totaled 40 people who were health cadres, members of the Indonesian doctor's wife association and family doctors in the city of Bandar Lampung. The results of the evaluation of the implementation of community service found that there was an increase in the understanding of the participants by 92.5% to a good understanding, 7.5% of the participants had a fairly good understanding, and no participants had a lack of understanding regarding a healthy lifestyle and fulfilling balanced nutrition for children to prevent malnutrition. The average pre-test result was 57,3 and there was an increase in the post-test result, which was equal to 83. Based on the analysis using the Wilcoxon test, it was found that there was a statistically significant difference in the mean pre-test and post-test scores of the service participants (p=0,000). Activities to increase community participation to fulfill balanced nutrition for children based on food consumption as an effort to prevent malnutrition such as stunting have proven effective.